Maintenance of Grounding Systems at Distribution Substations to Improve The Reliability of Electricity Distribution in The Work Area of PLN Customer Service Unit at Bima City - Muhamad Aswin Yusrih, Aditama; Wiryajati, I Ketut; Djul Fikry, Budiman (Depertment of Electrical Engineering University of Mataram, 2025)
Distribution substations have an important role in maintaining the reliability of the electricity distribution system. In the working area of PLN ULP Bima City, disturbances often occur due to high grounding resistance values, declining equipment conditions, and external factors such as weather. These problems reduce system performance and increase the risk of electrical disturbances. The solution applied is measurable grounding maintenance using field inspection methods, technical interviews, and literature studies. The contribution of this activity is the preparation of an effective distribution substation maintenance procedure that complies with PLN standards. The methods used include predictive, preventive, and corrective maintenance, as well as replacement of components such as arresters, insulators, and A3CS cables. The results showed an initial resistance value of 18.22 Ω which dropped to 1.49 Ω after the installation of a new grounding system and integration with arresters. This decrease proves the effectiveness of the applied method in lowering the ground resistance and improving protection against lightning strikes. Maintenance also includes testing using a Hioki FT6031 Earth Tester with results that meet PLN standards. In conclusion, thorough grounding maintenance is able to improve the reliability of distribution substations and reduce potential interference, as well as support the reliability of electricity supply in the Bima City area in a sustainable manner